Impact of Tailored Interventions to Reduce Drug Use and Sexual Risk Behaviors Among Homeless Gay and Bisexual Men. (March 2017) - Nyamathi, Adeline; Reback, Cathy J.; Shoptaw, Steven; Salem, Benissa E.; Zhang, Sheldon; Yadav, Kartik
A randomized controlled trial was conducted with homeless gay and bisexual men to assess the impact of two culturally sensitive intervention programs on reduction of drug use and risky sexual behavior. In this study, gay and bisexual men between 18 and 46 years of age were randomly assigned to one of two culturally sensitive behavioral intervention programs: a Nurse Case Management Plus Contingency Management (NCM + CM; n = 204) or a Standard Education Plus Contingency Management (SE + CM; n = 210) program. Regardless of group assignment, significant and clinically relevant reductions were observed in stimulant use over time. Multivariable predictors of stimulant use at 4- and 8-month follow-up evaluations were recent injection drug use, tested positive for HIV, or for use of amphetamine. Data revealed a significant linear decline over time for those who had sex with multiple partners. Furthermore, being HIV positive was associated with reporting multiple partners, while higher homophobia scores and having children were inversely related to reports of having sex with multiple partners at follow-up. Culturally sensitive approaches are needed to successfully reduce drug use and risky sexual activities among gay and bisexual populations.